Research on the Cultivation Path of Cross- Border e-Commerce Talents in Colleges and Universities Under the New Situation - Tang, Yan; Li, Leiming (Journal of Theory and Practice of Contemporary Education, 2024)
The strategic background of the new situation not only brings huge historical opportunities to cross- border e-commerce companies, but also puts forward new requirements for cross-border operators. This paper studies from the aspects of human resource development mode, internal and external infrastructure, quality education, etc., in order to promote the vigorous development of guangxi's cross-border industries.